The Relationship Between the Application of Lecture and Discussion Learning Methods to Learning Outcomes in Research Method Courses at the Bhakti Asih Midwifery Academy, Ciledug - Albahra Albahra; Partono Siswosuharjo (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
The purpose of this study was to determine differences in discussion and lecture learning methods on post-test scores in the Research Methods course for students at the Bhakti Asih Midwifery Academy, Ciledug. This research is an experimental research design using the True-Experiment Posttest Only Control Group Design. The data used are primary and secondary data with research instruments in the form of questionnaires in the control class and experimental class and secondary data about the results of student learning evaluations. The population of this study was 142 respondents. Retrieval of this research data is random sampling as many as 90 respondents. Data analysis used bivariate analysis with the Wilcoxon nonparametric T-Test method. The results showed that the average post-test score for the experimental group was 95.00, while that for the control group was 81.00.